Pemanfaatan Limbah Kaca Menjadi Batako di Desa Wisata Sukunan, Kelurahan Banyurraden, Kecamatan Gamping, Kabupaten Sleman, Yogyakarta - Firman Zaenal Arifin; Agus Riyadi (Prosiding Sains dan Teknologi, 2022)
The problem of waste will be more complex with the increase in population and since a few decades ago changes in consumption patterns and people's lifestyles have resulted in an increase in the amount of waste generation. Yogyakarta has a tourist village that is engaged in the environmental sector, to be precise, Dukuh Sukunan, Banyurraden Village, Gamping District, Sleman Regency, DIY. Glass waste is a waste that is mostly generated from people's lives, especially in big cities such as Yogyakarta and other cities. Most of the glass waste is directly dumped into open land, this of course will pollute the environment considering that glass is a sharp object that is difficult to decipher. One of the efforts to utilize this waste is as a substitute material for the brick mixture. Glass powder/glass powder has pozzolandic properties so that it can function as a substitute for cement and filler. The purpose of this study was to determine the general description of the use of glass waste into bricks, the quality of bricks, and the benefits of bricks for local residents. The method used is descriptive. Production of bricks in the village-scale Sukunan tourism village using a semi-manual method, the size of the bricks is 20x10x5 cm. brick quality according to SNI-03-0348-1989 standard. Brick with the age of 3 days is included in the class III category, which is 40 kg 7 days and 14 days is included in the class II category, which is 79 kg, while the bricks aged 21 and 28 are included in the class I category with the provisions of 100 kg and the compressive strength of the bricks is age 21 and 28 days are 102 kg and 112 kg (Rachaman, 2021). Brick is used commercially and socially. Keywords: Waste Glass, Tourist Village, Brick